2014
DOI: 10.1590/s0100-204x2014000200003
|View full text |Cite
|
Sign up to set email alerts
|

Teores foliares de fósforo e zinco, produtividade e crescimento de café irrigado

Abstract: Resumo -O objetivo deste trabalho foi avaliar os efeitos da irrigação sobre as concentrações foliares de P e Zn e sobre a produtividade e o crescimento do cafeeiro (Coffea arabica), cultivado em plantio tradicional e adensado. Utilizou-se o delineamento experimental de blocos ao acaso, em arranjo de parcelas subdivididas, com quatro repetições. As parcelas corresponderam às densidades de plantio (3.333 e 10.000 plantas ha -1 ), e as subparcelas corresponderam às lâminas d'água, aplicadas por quatro manejos de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
1
7
0
2
Order By: Relevance
“…It was observed that, even if the management operations (fertilization, control of diseases, among others) are performed in the entire area, this will not result in uniformity of yield in the plantation. Yield variation is influenced by factors such as: biennuality (Camargo & Camargo, 2001); soil fertility and leaf nutrition (Wadt & Dias, 2012;Scalco et al, 2014); occurrence of pests, diseases and weeds (Fialho et al, 2011;Carvalho et al, 2012;Lopes et al, 2012), among others.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that, even if the management operations (fertilization, control of diseases, among others) are performed in the entire area, this will not result in uniformity of yield in the plantation. Yield variation is influenced by factors such as: biennuality (Camargo & Camargo, 2001); soil fertility and leaf nutrition (Wadt & Dias, 2012;Scalco et al, 2014); occurrence of pests, diseases and weeds (Fialho et al, 2011;Carvalho et al, 2012;Lopes et al, 2012), among others.…”
Section: Resultsmentioning
confidence: 99%
“…Esses resultados corroboram com os relatos de Rezende et al (2010) e Scalco et al (2014) de que a utilização da fertirrigação potencializa a absorção de nutrientes pelo cafeeiro, dentre eles o fósforo, facilitando sua movimentação no perfil do solo e melhorando seu aproveitamento pelas plantas. Reis et al (2011) ) no cafeeiro em primeiro ano de produção.…”
Section: Mêsunclassified
“…Resultados recentes de pesquisas apontam que condições adequadas de umidade favorecem a absorção de nutrientes, em especial daqueles cujo mecanismo principal de transporte no solo é a difusão, como é o caso do fósforo (Costa et al, 2006;Oliveira et al, 2010). Assim, o uso da irrigação e da fertirrigação é uma das formas de maximizar a disponibilidade de fósforo no solo para que seja aproveitado de forma eficiente pelo cafeeiro (Scalco et al, 2014).…”
Section: Introductionunclassified
“…According to Scalco et al (2014) the search for information on plant response to nutrient absorption in densified and conventional crop cultivation under irrigated systems is of great importance, and these certainly differ from rainfed crops. The nutritional status of plants grown under irrigation and fertigation has been the subject of concern by coffee producers since the adoption of these systems has expanded in Brazil (Assis et al, 2015).…”
Section: Introductionmentioning
confidence: 99%